Assessment of Community Sensitivity to Air Pollution and Its Health Effects in Some Cities in Nigeria - Adione, Agatha Alami; Sangotayo, Emmanuel Olayimika; Olojede, Moses Abiodun (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
Air pollution is a significant problem in Nigeria due to its negative effects on human health. This study is an empirical investigation into how local populations in Nigeria evaluate the impact of air pollution on public health. A structured questionnaire was used and distributed via an online Google form. One hundred thirty respondents provided information regarding the relationship between air pollution and its health effects in 6 cities in Nigeria. The analysis utilized descriptive and inferential statistics, and the data was statistically evaluated using the chi-square and ANOVA with a 95% confidence level. The mean and standard deviation values of respondent’s sex are 65 and 84.8, respectively. The mean and standard deviation of the respondent’s age are 43 and 35 years, where 4% were female (n = 5) and 96% were male (n = 125). The two inferential statistics revealed that the city did not significantly influence the health treatment, whereas the health treatment preferences were significantly affected by the city and the age range. Respondents are aware of air pollution in their communities and acknowledge that it is widespread; 41% of respondents strongly concurred and 55% agreed that air pollution and its adverse effects on health are prevalent. Consequently, people’s health will deteriorate and air pollution will negatively impact public health due to the significant health hazard. Public health is being seriously endangered as a direct result of the threats that are posed by airborne contaminants.